Atopic dermatitis in children: a clinico epidemiological study and the role of dietary restrictions in disease severity - Nadeem, Ahmed; V., Bindu; Riyaz, Najeeba (International Journal of Research in Dermatology, 2017)
Background: Atopic dermatitis is chronic or chronically relapsing inflammatory dermatoses. Immune sensitization to food derived allergens play an important role in its pathogenesis. Aim of this study was to assess the clinical and epidemiological aspects of atopic dermatitis in children below 12 years of age, the role played by dietary modifications in the severity of disease and to correlate serum IgE levels with clinical severity and dietary modifications. Methods: Seventy five patients, diagnosed as atopic dermatitis in age group of 1-12 years who attended Dermatology department in a tertiary care hospital during a 1 year period were selected. The clinico epidemiological features were noted. Patients were asked to avoid milk, egg and food containing milk and egg and other precipitating food for 3 weeks. SCORAD index and serum IgE levels was assessed initially and after 3 weeks.. Results: Of the 75 children with atopic dermatitis majority had pruritus and typical morphology of lesions .It was seen that 44% had food as their main precipitant; 26.7% inhalants, 22.7% seasonal variations and 6.7% had other precipitants including alternative medication. Mean SCORAD index of the cases and mean serum IgE values were decreased after 3 weeks of dietary restrictions. Conclusions: Food was found to be the major precipitant, followed by inhalants, seasonal variations and other medications. Egg, fish and milk were found to be the major precipitants amongst food. There was a decline in SCORAD index and mean serum IgE after 3 weeks of dietary restriction.